Development and Validation of a Mathematics Learning Motivation Questionnaire for Middle-Grade Elementary Students - Jin Xue; Herdian (Research and Innovation in Social Science Education Journal (RISSEJ), 2024)
This study aimed to develop and validate the "Mathematics Learning Motivation Questionnaire for Middle-Grade Elementary School Students," focusing on cognitive drive, self-enhancement drive, and affiliated drive, to measure the mathematics learning motivation among middle-grade elementary students. The study was conducted in two phases using a sample of students from third and fourth grades in Nanjing, Nantong, and Hefei. Initially, a pilot phase (Study 1) involved administering the questionnaire to 129 participants to perform item analysis and ensure item discrimination. In the formal testing phase (Study 2), the refined questionnaire was administered to a larger sample of 381 students to assess reliability and validity through item-total correlation. The questionnaire demonstrated significant discriminative capacity, with all items showing notable differences in motivation levels between high and low scorers. The reliability analysis yielded a Cronbach's Alpha of 0.949, indicating high reliability. However, items with low correlation coefficients in the pilot phase were removed to enhance the tool’s focus and validity. The study’s geographical limitation to specific regions might affect the generalizability of the findings. Additionally, the design of the questionnaire, while comprehensive, did not fully account for the discriminant validity due to the constrained development time. The "Mathematics Learning Motivation Questionnaire for Middle-Grade Elementary School Students" provides a reliable and valid tool for assessing student motivation in mathematics. Future research should expand the scope to include a more diverse geographic sample and employ longitudinal designs to explore motivational changes over time, enhancing the tool’s applicability and effectiveness in diverse educational contexts.